Genome-wide association analysis and KASP markers development for protein quality traits in winter wheat - Yousheng Tian; Pengpeng Liu; Dezhen Kong; Yingbin Nie; Hongjun Xu; Xinnian Han; Wei Sang; Weihua Li (BMC Plant Biology)
Abstract Background Wheat (Triticum aestivum L.) is a significant cereal crop that plays a vital role in global food production. To expedite the breeding of wheat cultivars with high protein quality, it is necessary to genetically analyze the traits related to quality. A genome-wide association study (GWAS) was conducted to identify the genomic regions responsible for protein quality traits in winter wheat. Results Six protein quality traits were evaluated across two locations and two years for a total of 341 wheat accessions. Utilizing the wheat 40 K SNP array, GWAS identified 97 significantly stable SNPs at 43 loci for five out of six protein quality traits using a linear mixed model. The 43 loci distribution was four for grain protein content, two for flour protein content, one for wet gluten content, four for gluten index, and thirty-two for Zeleny sedimentation value. The most significant associations were identified on chromosomes 1 A, 1B, and 1D. Haplotype analysis of loci associated with the gluten index in the 412–416 Mb interval on chromosome 1D identified three blocks. Accessions with superior haplotypes showed a significantly higher gluten index than those with inferior haplotypes. Six KASP markers were successfully developed for the gluten index, while five KASP markers were developed for the Zeleny sedimentation value. Additionally, eight candidate genes were identified that may affect protein accumulation during grain development. Conclusions Our study identified 97 SNPs significantly associated with protein quality traits; developed 6 KASP markers for gluten index, and 5 KASP markers for Zeleny sedimentation values; screened 8 candidate genes that may be related to protein quality during grain development. Thise research will offer valuable insights for wheat breeding programs in China and globally.